Trigonometric Approximations for Some Bessel Functions - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
Formulas are obtained for approximating the tabulated Bessel functions Jn(x), n = 0–9 in terms of trigonometric functions. These formulas can be easily integrated and differentiated and are convenient for personal computers and pocket calculators.